Learning How to Use Input-Based and Output-Based Form-Focused Instruction: A Meta-Analytic Comparison of Korean and Persian EFL Learners - Andrew Schenck (Journal of Linguistics and Language Teaching)
Although Form-Focused Instruction (FFI) has been extensively investigated, the degree to which grammatical difficulty impacts input-based and output-based FFI approaches has yet to be well defined in an English as a Foreign Language (EFL) context. To address the need for further research, 36 experimental studies were selected for metanalysis (18 studies with Korean EFL learners and 18 studies with Persian EFL learners). The effects of the type of instruction (input vs. output) were analysed along with other variables that may affect acquisition (complexity of a target feature and L1). The results suggested that input-based instruction was more effective for smaller phrasal features, while output-based instruction was more effective for features with more complex clauses (e.g., relative clauses or conditionals). Regarding the L1, output-based emphasis of collocations was more effective with Persian EFL learners, whose L1 shares more morphosyntactic similarities with English. Collectively, both L1 and L2 may determine the efficacy of FFI.